'Professional partner' or 'management's bitch'?: a discourse analytic study of the identity construction of HR practioners in English local government - Kinsey, Sue (2012)
Drawing on the transcripts of 47 semi-structured interviews with HR practitioners in local government in the English Midlands, this thesis explores what Beech (2008) calls the ‘route to meaning construction of the self’ of HR practitioners as they navigate discourses of HRM and public sector reform in the pursuit of ‘professional’ identity and organizational legitimacy. Through the use of discourse analysis, the study makes three key contributions: firstly, it challenges the dichotomous characterisation of a ‘modernising’ public sector and identifies a discursive pragmatism, whereby public sector employees craft a workable identity reconciling ‘old’ public sector talk with a tempered public sector ‘reform’ discourse to forge ‘third way’ discourses. Secondly, it challenges the notion of ‘strategic’ legitimacy as the only means by which a plausible organizational identity might be constructed for the HR function, with the denigrated ‘administrative’ HR role rewritten as a problem solving and pragmatic orientation. Finally, it concludes that HR legitimacy will remain elusive whilst HR’s identity, particularly in relation to line management, is constructed through gendered and sexualised discourses. The title of the thesis, drawing on the words of interviewees, represents alternative conceptions of the HR function: legitimated through recourse to ‘professionalism’ and partnership talk, or managerial cipher, in thrall to public sector managerialization, particularly through the construction of HR’s role and identity in gendered and sexualised terms.